The Unbearable Presence of the Modern Project - Winckler, Carlos Roberto (2008)
The work refers to Habitasul financial institutions and to the crisis in which they were involved, the peak of which occurred in February 1985, with the intervention of the Central Bank of Brazil, which resulted in a significant reduction in the Group's activities in the financial area. The basic focus is the analysis of the behavior of the press in the central episodes and in those that preceded and succeeded them, in light of the concepts of informative journalism.